The story of Apollonius, King of Tyre : a study of its Greek origin and an edition of the two oldest Latin recensions - Kortekaas, G. A. A. (Mnemosyne, Supplements, 2004)
The story of Apollonius King of Tyre has rightly been called the most popular romance of the Middle Ages. From Iceland to Greece, from Spain to Russia, versions of this novel are recorded. It is the variation among the Latin versions and the numerous vernacular adaptations that make this story especially interesting. Shakespeare used and adapted it in his Pericles, Prince of Tyre. Its plot continues to fascinate us. Incest, deception, pirates, famine, sex and shipwreck form its tasty ingredients. Its links with the Greek novel, which today stands in the centre of scholarly interest, are striking. In this book the author attempts to show that the novel originated in Greece, or more precisely Asia Minor, possibly in Tarsus. A graffito from Pergamum and a coin struck in Tarsus at the time of Caracalla's visit (215 AD) support his conviction. All these aspects make the present book attractive to scholars of many different disciplines.